PENERAPAN AKUNTANSI MANAJEMEN: ADOPSI TEKNOLOGI, PENGETAHUAN, PERSEPSI SERTA DAMPAKNYA BAGI KINERJA UKM - Krisdiyawati Krisdiyawati; Hikmatul Maulidah (Jurnal Proaksi, 2023)
Management accounting in decision making used focuses internally on both financial and non-financial information. The purpose of this study is to examine the adoption of technology, perceptions and knowledge of SMEs on the application of management accounting, and analyze the performance of SMEs on the application of management accounting. This research is with a descriptive and verifiative approach from primary data through the distribution of questionnaires. The population is obtained from SME owners in West Tegal District. The number of samples was obtained by 50 SMEs through sampling techniques with simple purposive sampling techniques and adata analysis using SmartPLS. The results showed , of SME performance has a significant influence on the application of management accounting. Thework of SMEs as a mediating variable has an influence on the knowledge and perception of SMEs on the application of management accounting. Only the variable of technology adoption is not able to mediate the work of SMEs and does not have a significant effect on the application of management accounting. The application of management accounting plays a role in decision making to improve SME performance resulting in better business development.